Design and Optimization of Polarization Splitting and Rotating Devices in Silicon-on-Insulator Technology. (6th February 2014) - Troia, Benedetto; De Leonardis, Francesco; Lanzafame, Mauro; Muciaccia, Tommaso; Grasso, Giuseppe; Giannoccaro, Giovanni; Campanella, Carlo Edoardo; Passaro, Vittorio M. N.
Abstract : We review polarization splitting and rotating photonic devices based on silicon-on-insulator technology platform, focusing on their performance and design criteria. In addition, we present a theoretical investigation and optimization of some rotator and splitter architectures to be employed for polarization diversity circuits. In this context, fabrication tolerances and their influences on device performance are theoretically estimated by rigorous simulations too.